X-ray indices of chest drain malposition after insertion for drainage of pneumothorax in mechanically ventilated critically ill patients - Mokotedi, Masego Candy; Lambert, Lukas; Simakova, Lucie; Lips, Michal; Zakharchenko, Michal; Rulisek, Jan; Balik, Martin (Journal of thoracic disease, 2018)
BACKGROUND: Chest drain (CD) migration in the pleural cavity may result in inadequate drainage of pneumothorax. The aim of this study was to assess several parameters that might help in diagnosing CD migration on chest X-ray (CXR). METHODS: Patients with a CD inserted from the safe triangle with a subsequent supine CXR and CT scan performed less than 24 hours apart were assessed for CD foreshortening, angle of inclination of the CD, and CD tortuosity. CD foreshortening was expressed as a ratio between CD length measured in coronal plane only and CD length inside the pleural cavity measured on CT. The angle of inclination of the CD was measured as the angle between the horizontal line and CD at the pleural space entry on CXR. CD tortuosity was calculated as a ratio between the distance from CD pleural space entry to the tip of the CD and the length of CD from the pleural space entry to its tip on CXR. RESULTS: Altogether 28 patients were included in the study. The median time between the CXR and CT examinations was 5.4 hours (IQR, 3.8-6.9 hours). CD foreshortening was the best clue of a misplaced CD with AUC of 0.93, 100% sensitivity and 88% specificity for a cut-off value of 82%. The angle of CD inclination was greater in patients with misplaced CD with AUC of 0.83, 75% sensitivity and 92% specificity for a cut-off of 50 degrees. The performance of CD tortuosity was poor. CONCLUSIONS: Greater foreshortening of the CD and a steep angle of inclination of the CD above the horizontal at chest entry should raise suspicion of CD migration and mandate further investigation by chest ultrasound to rule out residual pneumothorax occult on CXR.
Keywords: chest drainage; chest X-ray (CXR); imaging, intensive care; Pneumothorax